Evolution paths of stakeholder-oriented smart transportation systems based on 5G - Risto Jurva; Marja Matinmikko-Blue; Tarja Outila; Virve Merisalo (International Telecommunications Society (ITS), 2021)
Societies are experiencing large-scale transformation through digitalization programs covering all private and public sectors. Digitalization advances also the growing demands of sustainable development, in which nations and cities all over the world have set ambitious targets. Transportation is one the cornerstone verticals of cities and has attracted wide attention from various stakeholders developing services and solutions for digitalization. In general, ICT solutions are in the core of digitalization and trailblazing technologies have been developed to enable modern transportation services. 5G technology covering wireless connectivity, IoT sensor technology, distributed edge computing, artificial intelligence, high power computing and service platforms offers numerous opportunities to the development of sophisticated smart transportation services. However, to adopt a pervasive approach for the evolvement of digital transportation services, it is important to examine the system level point of view. Developing occasional services for various transport modes without targeted inter-operability of services, the result of digitalization of transportation can be extremely fragmented. This paper aims to highlight the top-down angle of research and development of the smart transportation system. The development requires seamless co-operation of researchers and specialists of transport systems, urban design and planning and wireless technologies to integrate transport infrastructure, 5G wireless communication infrastructure and traffic management systems to enable advanced digital services for all transport modes. Moreover, this article introduces the stakeholders recognized from transport systems, urban design and planning and wireless technologies. The role of each stakeholder is described a like.
Keywords: 330